Human Resource Management Model in Islamic Boarding School-Based Private Madrasah Tsanawiyah - Dery Jamaludin Basari; Saliha Sebgag; Sayid Muhammad Rifqi Noval; Achmad Mudrikah; Agus Mulyanto (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
The development of madrasahs cannot be separated from the productive human resources in them. Productive human resources cannot be separated from good management. This management is known as human resource management. In managing human resources, the madrasah must be able to create a management model that is planned, structured, and measurable in order to produce quality human resources. The human resource management model at Islamic boarding school-based Madrasah Tsanawiyah has its own uniqueness in achieving the vision of the institution. Starting with the main competencies that correspond to the institution's dominance and the continuity of human resources who always carry out service to the institution. The human resource management model in Islamic boarding schools begins with the stages of carrying out job analysis, implementing recruitment, implementing HR placement, implementing HR development, implementing compensation, implementing integration, implementing HR maintenance, implementing termination of employment, and last is the implementation of HR monitoring and assessment stages.